PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PKN MATERI BELA NEGARA PADA SISWA KELAS IX C SMP NEGERI 3 BATURETNO SEMESTER GASAL TAHUN PELAJARAN 2018/2019 - Sri Hastuti (Universitas Sahid Surakarta, 2020)
In implementing learning, the teacher must be able to select and use learning media that is in accordance with the characteristics of the material, and the student's environment. The TPS learning method using State Defense material can increase learning outcomes and interest in Class IXC students of SMP Negeri 3 Baturetno in the 2018/2019 academic year. This is interesting to study in the form of classroom action research.This research is a Classroom Action Research (PTK). The research subjects were students of Class IX C SMP Negeri 3 Baturetno, totaling 28 students. Data collection techniques using written test methods, observation, documentation. The research procedure was carried out in two cycles and each cycle consisted of planning, implementing, observing and reflecting. The results of this study were able to answer the problem formulation, achieve the research objectives and answer the action hypothesis, namely: (1) there was an increase in learning outcomes, this can be seen from: (a) an increase in student learning completeness when compared between pre-cycle, namely 9 students (32%) at the end. cycle 2 to 24 students (86%) so that they have reached the predetermined level of completeness, namely 75%; (b) there is an increase in the average value when compared between pre-cycle 58.57 at the end of cycle 2 to 70.17. (2) there is an increase in interest in learning when compared between pre-cycle cycles, namely the average value of 66.92 (sufficient) increases at the end of cycle 2 to 90.97 (very good). This study concludes that the use of the TPS learning method with state defense material can improve learning outcomes and interest in learning Civics for Class IX C students of SMP Negeri 3 Baturetno in 2018/2019 school year.